Activation of the Kynurenine Pathway in Human Malignancies Can Be Suppressed by the Cyclin-Dependent Kinase Inhibitor Dinaciclib - Riess, Christin; Schneider, Björn; Kehnscherper, Hanna; Gesche, Julia; Irmscher, Nina; Shokraie, Fatemeh; Classen, Carl Friedrich; Wirthgen, Elisa; Domanska, Grazyna; Zimpfer, Annette; Strüder, Daniel; Junghanss, Christian; et al. (Frontiers in Immunology, 2020)
Indoleamine 2, 3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO2) are the key enzymes of Tryptophan (TRP) metabolism in the kynurenine pathway (KP). Both enzymes function as indicators of immunosuppression and poor survival in cancer patients. Direct or indirect targeting of either of these substances seems thus reasonable to improve therapy options for patients. In this study, glioblastoma multiforme (GBM) as well as head and neck squamous cell carcinomas (HNSCC) were examined because of their different mechanisms of spontaneous and treatment induced immune escape. Effects on gene expression and protein levels were examined. Accompanying assessment of TRP metabolites from treated GBM cell culture supernatants was conducted. Our results show a heterogeneous and inversely correlated expression profile of TRP metabolizing genes among GBM and HNSCC cells, with low, but inducible IDO1 expression upon IFNγ treatment. TDO2 expression was higher in GBM cells, while genes encoding kynurenine aminotransferases were mainly confined to HNSCC cells. These data indicate that the KP is active in both entities, with however different enzymes involved in TRP catabolism. Upon treatment with Temozolomide, the standard of care for GBM patients, IDO1 was upregulated. Comparable, though less pronounced effects were seen in HNSCC upon Cetuximab and conventional drugs (i.e. 5-FU, Gemcitabine). Here, IDO1 and additional genes of the KP (KYAT1, KYAT2, and KMO) were induced. Vice versa, the novel yet experimental Cyclin-dependent kinase inhibitor Dinaciclib suppressed KP in both entities. Our comprehensive data implies inhibition of the TRP catabolism by Dinaciclib, while conventional chemotherapeutics tend to activate this pathway. These data point to limitations of conventional therapy and highlight the potential of targeted therapies to interfere with the cells’ metabolism more than anticipated.